Online Hadith in Cyber Media: Benefit, Challenging, and Solution - Nikmatullah, Nikmatullah (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2024)
This article aims to explore three aspects of hadith in online media: benefits, challenges, and solutions. Using a descriptive qualitative approach, data for this article were obtained from online media and social media, and supplemented by secondary data from previous research findings. The data were analyzed through three stages: restatement, description, and interpretation. This article concludes that online hadith benefits the online community by facilitating the sharing, learning, and practice of hadith easily, effectively, and efficiently. However, digital hadith faces challenges concerning the text, understanding, and practice of hadith. These challenges include distortions of hadith texts, the spread of false hadith, and the commodification of hadith for economic and political interests. To maintain the authenticity of hadith, it is necessary to verify the source of the hadith through Internet technology, by referring to the original books, or by consulting trustworthy ulama. It is imperative to read the Prophet's Hadith comprehensively and to consider the spirit of Islam as a solution to avoid conflicts arising from different understandings of the Hadith. This article describes the complexity of Hadith dissemination on the Internet and highlights the religious trends of contemporary Indonesian Muslim society.Â